Art appreciation in cultural arts subject - Wulandari Wulandari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2019)
This research begins with the finding that the students of class VII who do not appreciate the various arts presented by class IX on art performances held in school. This can be evidenced by the loneliness of his students watching art performances at school because the majority of VII grade students roam the school. As if not concerned with the various artistry that is displayed. This research uses qualitative method. Application of research informants conducted. Determination of research informants conducted by Purposive sampling. Data were collected using observation, interview and documentation techniques. The technique of guaranteeing the validity of the data guarantees the data of this study using triangulation, Data Analysis model Miles dab Hubberman method using three steps consisting of data reduction, data presentation and verification or conclusion. The result of the analysis shows that: the factors that cause the less appreciation of the students of VII and the students of class VII are: (1) the lack of students' understanding of the displayed art, (2) the interesting or unattractive influence of art displayed, (3) puberty, of them come to school just to play around in groups. In the case of the highly needed teacher's ability in the field of art and culture studies to more in depth provide learning to students of class VII and class VIII so they are more appreciative, and can assess every art that is displayed.